2021
DOI: 10.1111/ele.13719
|View full text |Cite
|
Sign up to set email alerts
|

Disease and fire interact to influence transitions between savanna–forest ecosystems over a multi‐decadal experiment

Abstract: Global change is shifting disturbance regimes that may rapidly change ecosystems, sometimes causing ecosystems to shift between states. Interactions between disturbances such as fire and disease could have especially severe effects, but experimental tests of multi‐decadal changes in disturbance regimes are rare. Here, we surveyed vegetation for 35 years in a 54‐year fire frequency experiment in a temperate oak savanna–forest ecotone that experienced a recent outbreak of oak wilt. Different fire regimes determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Rebertus and Burns (1997) found that tree survival in Quercus savannas was inversely related to grass cover. At CCESR, grass abundance is strongly negatively associated with tree canopy cover in the oak‐dominated habitats (Pellegrini et al, 2021; Peterson et al, 2007). In a separate CCESR study, Wragg et al (2018) showed that, compared to forbs, grass‐dominated areas generate higher temperatures, release heat to greater heights and burn more completely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rebertus and Burns (1997) found that tree survival in Quercus savannas was inversely related to grass cover. At CCESR, grass abundance is strongly negatively associated with tree canopy cover in the oak‐dominated habitats (Pellegrini et al, 2021; Peterson et al, 2007). In a separate CCESR study, Wragg et al (2018) showed that, compared to forbs, grass‐dominated areas generate higher temperatures, release heat to greater heights and burn more completely.…”
Section: Discussionmentioning
confidence: 99%
“…The site is a mosaic of wetlands, old fields, and patches of oak savannas, woodlands and forests. CCESR experiences a temperate mesic climate (780‐mm mean annual precipitation and 6.72°C mean annual temperature; Pellegrini et al, 2021). Except for that in a few small wetland patches, the soil in the area of CCESR where this study was conducted is of the Sartell series, excessively drained and low in organic matter and total nitrogen (Grigal et al, 1974).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible, then, that oak wilt might have reduced the neighbor benefits over time. However, in a separate study at CCESR, Pellegrini et al (2021) found that while oak wilt dramatically increased tree mortality in unburned areas, where trees are densely packed and which are dominated by Q. ellipsoidalis , it had little effect in frequently burned sites. Also, since species in the red oak group lack tyloses, they are not as able to effectively compartmentalize scarring injuries as are white oaks, thereby making them considerably more susceptible than white oaks to subsequent fungal infection (Gibbs and French 1980, Juzwik et al 2011, Dey and Schweitzer 2018.…”
Section: Survivalmentioning
confidence: 93%
“…A second possible explanation for the decline in the strength of neighbor facilitation involves the arrival of oak wilt (Bretziella fagacearum ) in east-central Minnesota several decades ago (Gibbs and French 1980), and which is thought to have spread rapidly at CCESR since 2010 (Sapes et al 2021, Pellegrini et al 2021). The fungus is spread primarily through root grafting among neighboring trees and by sap beetles (Nitidulidae) (Kuntz andRiker 1956, Jagemann et al 2018).…”
Section: Survivalmentioning
confidence: 99%
“…The presence of oak wilt fungus has been documented in central Minnesota since the 1940’s where it has led to widespread mortality in forests not treated for the disease. At CCESR, the fungal pathogen oak wilt has spread rapidly in the last decade, leading to exponential increases in the number of standing dead trees as a result of recent mortality (Pellegrini et al, 2021). The diversity of tree species and the widespread presence of active oak wilt make CCESR well suited to assess the capacity of airborne spectroscopy to detect oak wilt in red oaks.…”
Section: Methodsmentioning
confidence: 99%